1999
DOI: 10.1093/oxfordjournals.jbchem.a022388
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Trypsin in Human Cancer Cell Lines and Cancer Tissues and Its Tight Binding to Soluble Form of Alzheimer Amyloid Precursor Protein in Culture

Abstract: It was recently found that overexpression of the trypsin gene in tumor cells stimulates their growth in culture and in nude mice. In the present study, expression of trypsin in various human cancer cell lines and tissues was studied by gelatin zymography and immunoblotting before and after enterokinase treatment and by immunohistochemistry. The analyses showed that many stomach, colon, and breast cancer cell lines secreted trypsinogens-1 and/or -2, as well as an unidentified serine proteinase of about 70 kDa, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
72
1
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 23 publications
5
72
1
4
Order By: Relevance
“…In this context, it is worth pointing out that several lines of evidence indicate the importance of locally secreted trypsin at the vicinity of colon tumours: (1) trypsin was shown to be expressed by the large intestine . Normal epithelial cells surrounding colon tumour cells are a likely source of active trypsin; (2) human colon cancer cells themselves were shown to express trypsin and trypsinogen (Bernard-Perrone et al, 1998;Miyata et al, 1999); (3) recent studies on gastric cancer indicate that blood vessels surrounding tumours express trypsin, whereas other blood vessels do not . Trypsin is also present in serum at nanomolar concentrations and could diffuse from blood to tumour cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it is worth pointing out that several lines of evidence indicate the importance of locally secreted trypsin at the vicinity of colon tumours: (1) trypsin was shown to be expressed by the large intestine . Normal epithelial cells surrounding colon tumour cells are a likely source of active trypsin; (2) human colon cancer cells themselves were shown to express trypsin and trypsinogen (Bernard-Perrone et al, 1998;Miyata et al, 1999); (3) recent studies on gastric cancer indicate that blood vessels surrounding tumours express trypsin, whereas other blood vessels do not . Trypsin is also present in serum at nanomolar concentrations and could diffuse from blood to tumour cells.…”
Section: Discussionmentioning
confidence: 99%
“…Extra-pancreatic production of trypsin was shown in ovarian (Hirahara et al, 1995), lung (Kawano et al, 1997), gastric and colonic tumours (Bernard-Perrone et al, 1998;Miyata et al, 1999); 2. The trypsinogen gene is significantly expressed in vascular endothelial cells around gastric tumours ; 3.…”
mentioning
confidence: 99%
“…Elevated levels of trypsin, the main endogenous PAR2 activator, have been found in a variety of tumors including colorectal carcinomas (8,9,51). Trypsin can also originate from vessels in the vicinity of the tumors (52) or could diffuse from blood to tumor cells.…”
Section: Par2 Transactivates Egf-r In Colon Cancermentioning
confidence: 99%
“…Extra-pancreatic production of trypsin was shown in ovarian (5), lung (6), gastric (7), and colonic tumors (8) and also in colon cancer cell lines (9,10). In addition, overexpression of exogenous trypsinogen cDNA in human gastric cancer cells increases their tumorigenicity in nude mice (7).…”
mentioning
confidence: 99%
“…14 -19 Trypsin also can stimulate tumor growth and enhance tumor adhesion to extra- cellular matrix components. 20,21 In previous studies, we demonstrated in pancreatic cancer cell lines that hepatic metastasis and invasive ability were correlated with amounts of cationic trypsinogen and were inhibited by a serine protease inhibitor. 24,25 Considering the results of this earlier work, secreted cationic trypsin is likely to degrade extracellular matrix components in several ways, including activating trypsinogen itself as well as latent proenzyme forms of other proteases.…”
Section: Discussionmentioning
confidence: 99%